STORE BRAND PURCHASE INTENTION: EFFECTS OF RISK, QUALITY, FAMILIARITY, AND STORE BRAND SHELF SPACE OF GIANT FACIAL TISSUE IN SURABAYA - Theresia Theresia; Christina R. Honantha; Dudi Anandya (CALYPTRA, 2020)
Abstract – This research is conducted to examine store brand purchase intention: effects of risk, quality, familiarity, and store brand shelf space of Giant facial tissue in Surabaya. A quantitative and causal type of research is adopted for this study. Questionnaire used was adopted from Dursun, Kabadayi, Alan, and Sezen (2011) for offline survey. Purposive sampling method was used in study. Sample consisted of 200 respondents, whose age is 18 years old or above and have bought and experience Giant facial tissue at least twice within six months in Surabaya. Further data analysis was analyzed by SPSS 23.0 and LISREL 8.0. Result shows that store brand shelf space and store brand familiarity has influence on consumer perceived risk and perceived quality of store brand in Surabaya. Moreover, store brand shelf space, store brand familiarity, perceived risk, and store brand perceived quality has influence on consumer purchase intention of Giant facial tissue in Surabaya.